1998
DOI: 10.1159/000026502
|View full text |Cite
|
Sign up to set email alerts
|

Pathological Regional Cerebral Blood Flow in Opiate-Dependent Patients during Withdrawal: A HMPAO-SPECT Study

Abstract: The aims of the present study were to investigate regional cerebral blood flow (rCBF) in heroin-dependent patients during withdrawal and to assess the relation between these changes and duration of heroin consumption and withdrawal data. The rCBF was measured using brain SPECT with 99mTc-HMPAO in 16 heroin-dependent patients during heroin withdrawal. Thirteen patients received levomethadone at the time of the SPECT scans. The images were analyzed both visually and quantitatively. A total of 21 hypop… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
39
0
4

Year Published

2001
2001
2018
2018

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 59 publications
(47 citation statements)
references
References 21 publications
(31 reference statements)
4
39
0
4
Order By: Relevance
“…Although a number of reports have shown that fluoxetine in the doses used in this study has no effect on DA levels in the accumbens (Clark et al 1996;Ichikawa and Meltzer 1995;Perry and Fuller 1992), one recent study found that similar doses of fluoxetine significantly increased DA levels in the frontal cortex (Gobert et al 1997). The frontal cortex is one area shown to be hypofunctional during opiate abstinence and withdrawal in human opiate addicts (Danos et al 1998;Gerra et al 1998;Krystal et al 1995) and it is possible that the treatments given in this study may be effective in changing preference by altering activity in this brain region.…”
Section: Discussionmentioning
confidence: 58%
“…Although a number of reports have shown that fluoxetine in the doses used in this study has no effect on DA levels in the accumbens (Clark et al 1996;Ichikawa and Meltzer 1995;Perry and Fuller 1992), one recent study found that similar doses of fluoxetine significantly increased DA levels in the frontal cortex (Gobert et al 1997). The frontal cortex is one area shown to be hypofunctional during opiate abstinence and withdrawal in human opiate addicts (Danos et al 1998;Gerra et al 1998;Krystal et al 1995) and it is possible that the treatments given in this study may be effective in changing preference by altering activity in this brain region.…”
Section: Discussionmentioning
confidence: 58%
“…The few studies that have investigated brain function in clients receiving MMT involved research participants who did not use illicit drugs (Rose et al, 1996;Krystal et al, 1995;Danos et al, 1998), as well as other that were actively using heroin (Pezawas et al, 2002) or were HIV-positive (Woods et al, 1991). The resultant reports yielded inconsistent findings of cortical and subcortical perfusion defects.…”
Section: Introductionmentioning
confidence: 99%
“…La mayoría de estos estudios han utilizado la Tomografía Computerizada por Emisión de Fotón Único (SPECT, del inglés Single Photon Emission Computerized Tomography). Todos refieren un menor flujo sanguíneo en el córtex prefrontal, frontal, temporal y parietal (Pezawas, Fischer, Podreka, Schindler, Brucke, Jagsch et al, 2002;Danos, Kasper, Grunwald, Klemm, Krappel, Broich et al, 1998;Gerra, Calbiani, Zaimovic, Sartori, Ugolotti, Ippolito et al, 1998;Krystal, Woods, Kosten, Rosen, Seibyl, van Dyck et al, 1995). Dos estudios refieren asimetrías en cuanto a la actividad, pues ésta era menor en las zonas cerebrales derechas respecto a las izquierdas, alegando que dicha asimetría puede deberse más al estado anímico de los sujetos que a la propia administración crónica.…”
Section: Neuroimagen De La Dependencia De Opiáceosunclassified